Effect of nitrogen and potash application on yield and quality of china hybrid tea (Camellia sinensis) grown in Kangra valley of Himachal Pradesh - SHARMA, D K; SHARMA, K L (The Indian Journal of Agricultural Sciences, 2013)
A 140-year-old dark leaf china hybrid tea [Camellia sinensis (L.) O.Kuntze] section was fertilized with 4 levels of nitrogen (0, 60; 120, 180 kg/ha) and 4 levels of potash (37.5, 75.0, 112.5, 150 kg/ha) at constant level of phosphate (39 kg/ha) since 1988. Yield responses have been presented for 6 years from 1988-93 averaged over 2-3 years pruning cycles. Nitrogen application up to 60 kg/ha increased the yield and declined thereafter. Application of potash responded up to 75 kg/ha and had a decreasing effect thereafter in a regular fashion. The synergistic effect of N6o with k75 was significantly achieved over a period of 6 years and the largest crop to the extent of 1 722 kg made tea/ha was harvested at N60 P39 K75 fertilization level. As regards quality of made tea in terms of total colour and per cent brightness, the highest values were found in no-nitrogen application, whereas the same character was improved with the application of potash.